Identify the concentration of some heavy metal elements in different types of marine sediments dispersed on Lattakia and Banias coast (Latakia University Journal -Basic Sciences Series, 2018)
This research focuses on identifying the concentration of some heavy metal elements (Lead (Pb), manganese (Mn), nickel (Ni), copper (Cu), cadmium (Cd)), in different types of marine sediments dispersed along Latakia and Banias coastal area during spring period of 2015using the Atomic Absorption (Atomic Absorption Spectrophotometer: AAS). The samples were collected fromregions differ from each other in terms of geographical location and nature of the pollutants.The results of the research indicate a correlation between the change in the concentration of studied elements (Pb, Ni, Cu, Mn& Cd) and the nature and quality of the sand on one hand, and the different sources of pollution and its role in changing the concentration of these elements values on the other hand. The results also showed that the fine sand are dominant in the Latakia beachcompared with Banias sediments where medium and coarse sand are dominant.The results also showed that the concentration of manganese (361.33-968.54mg / kg) and lead (25.09 - 169.51mg / Kg) is high in both sites, while there was a clear spatial changes reflected in the low concentration of both copper ( 83.72-272.22mg / kg) and nickel (99.55-132.11mg / kg) and high concentration of cadmium (5.92-11.25μg / kg) in the samples of Banias beach compared with the samples taken from Latakia beach (285.01-620.11mg / kg, 53.85-390.61 mg / kg and 3.33-5.31μg / kg, respectively).